2022
DOI: 10.3390/healthcare10091745
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Roles of Anxiety, Depression, Sleepiness, Insomnia, and Sleep Quality in the Association between Problematic Social Media Use and Quality of Life among Patients with Cancer

Abstract: The present study examined the mediating role of anxiety, depression, sleepiness, insomnia, and sleep quality in the association between problematic social media use and quality of life (QoL) among patients with cancer. This cross-sectional survey study recruited 288 patients with cancer to respond to measures on anxiety, depression, sleepiness, insomnia, sleep quality, problematic social media use, and QoL. Structural Equation Modeling was used for the mediation analysis. There were significant relationships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
2
4
0
Order By: Relevance
“…This indicates that as one of the variables increases, the other variable may also increase and vice versa. This is consistent with the findings of previous studies [ 7 , 10 , 33 , 34 ]. In addition, there was an indirect association between problematic social media use and psychological distress via selfitis.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…This indicates that as one of the variables increases, the other variable may also increase and vice versa. This is consistent with the findings of previous studies [ 7 , 10 , 33 , 34 ]. In addition, there was an indirect association between problematic social media use and psychological distress via selfitis.…”
Section: Discussionsupporting
confidence: 94%
“…The other relationships were significantly positive, indicating that as one of those variables increases, the other also increases and vice versa. The current relationships are consistent with the findings of previous studies [ 7 , 8 , 10 , 31 , 32 , 39 ]. It is noteworthy that the present study is the first to objectively establish a known relationship between problematic smartphone use and selfitis although there have been inferred relationships between them [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is so because there are risks associated with social media use; unfortunately, some studies opt to report social media benefits, ignoring the risks [ 11 ]. Such risks are demonstrated by Imani et al [ 12 ], who indicated that there was an association between social media use and quality of life among people with depression and anxiety.…”
Section: Introductionmentioning
confidence: 96%